Assessing upper limb function with ALSFRS-R in amyotrophic lateral sclerosis patients. Issue 5 (3rd July 2019) - Pinto, Susana; Gromicho, Marta; de Carvalho, Mamede
Abstract: Background : Functionality in ALS is usually assessed by the revised functional ALS rating scale (ALSFRS-R). The impact of dominant vs. non-dominant side of upper limb (UL) onset on functionality has not been addressed before. Methods : Consecutive patients with clear UL side dominance and followed in our unit were included. We considered three groups accordingly to side-of-onset: right (RUL), left (LUL) and bilateral UL onset forms. Patients were evaluated with ALSFRS-R, including its respiratory (RofALSFRS-R), bulbar (ALSFRSb), UL (ALSFRSul), and lower limb (ALSFRSll) subscores. T-test and X2 assessed differences. Patients were further compared regarding differences in writing (4th question, Q4, in the ALSFRS-R). A p  < 0.01 was considered as meaningful. Results : From the 109 patients (75 men; mean onset age 61.36 ± 13.6; mean disease duration 23.1 ± 28.1 months), 65 had RUL, 38 LUL, and 6 bilateral UL onset forms. Right-side dominance was identified in 104. Patients with writing difficulties (87 in 109) had significantly lower ALSFRS-R and ALSFRSul ( p  < 0.001), presenting more problems in dressing ( p  < 0.001) and personal hygiene ( p  = 0.006). RUL patients had significantly lower Q4 scores than LUL ( p  = 0.002). No other differences were found between these two groups, including ALSFRS-R ( p  = 0.257) and ALSFRSul ( p  = 0.051). Functional impact on UL scores was similar between RUL and bilateral onset patients. Q4 scores were negatively influenced by hand-dominance in RUL patients ( p  = 0.007). Conclusions : ALSFRS-R is an important tool to assess functional UL involvement in ALS. However, it can mislead clinicians when evaluating right-handed patients with initial LUL onset form. Hand dominance should be considered in ALS functional assessment.